Identification of cutaneous arteries of the perineal and caudal thigh region: A cadaveric study in 12 cats. Issue 2 (18th November 2019) - Andries, Courtney V.; Degner, Daniel A.; Ibrahim, Mohammed
Abstract: Objective: To describe the location of the dorsal perineal artery in cats and identify landmarks for axial pattern flaps based on this vessel. Study design: Anatomic study. Animals: Twelve feline cadavers. Methods: Nonselective barium sulfate angiography was performed via injection of the descending aorta. Skin excised from the perineum and thighs was evaluated via gross inspection and radiography to identify angiosomes. Results: The dorsal perineal artery had a robust angiosome on the caudal thigh in 10 of 12 cadavers. The artery exited the ischiorectal fossa along the muscular furrow between the biceps femoris and semitendinosus muscles and passed sagittally toward the popliteal fossa in those 10 specimens. All cadavers had a consistent angiosome based on the ventral perineal artery, which was located on the caudomedial thigh. All cadavers also had a consistent angiosome from a cutaneous branch of the popliteal artery, which traveled in a distal to proximal direction starting at the popliteal fossa. Conclusion: The dorsal perineal artery had a large cutaneous angiosome on the caudal thigh, which was consistent in most cats. The ventral perineal artery and cutaneous branch of the popliteal artery had consistent but smaller cutaneous angiosomes. Clinical significance: The axial pattern flaps of the cutaneous branches of the dorsal and ventral perineal arteries and the popliteal artery provide a robust arterial blood supply to the skin of the perineum and the caudal thigh. These three flaps may therefore have adequate vascular supply to consistently survive in most cats.